Effects of socially appropriate singing on the vocal stereotypy of children with autism spectrum disorder. (28th January 2020) - Thomas, Benjamin R.; Charlop, Marjorie H.; Lim, Nataly; Gumaer, Caitlyn
Abstract: This study evaluated the effects of children with autism spectrum disorder engaging in socially acceptable singing on their vocal stereotypy. A multiple‐baseline across four participants with embedded multielement designs was used to assess the effects of the singing intervention upon later occurrence of vocal stereotypy for each participant. Results showed that fewer instances of vocal stereotypy occurred during and after singing intervention sessions. Additionally, two children began to emit appropriate singing after intervention, which suggests that the topography of their vocal stereotypy (e.g., monosyllabic or screeching sounds) was altered to some extent. Overall, results suggest positive implications for teaching appropriate vocal behaviors as functional replacements for vocal stereotypy.